Investigating The Status of Local Government Education Authority in Providing Quality Learning Environment in Gombe Local Government Area of Gombe State - Bappah, A. (Kashere Journal of Education, 2021)
This study investigated the status of Local Government Education Authority in providing quality Learning Environment in Gombe Local Government Area; two objectives were used to guide the study. The study adopted survey research design, the population of the study comprised of 2,244 total number of teaching staff and head teachers in which 327 respondents were selected using simple random sampling. A four-point rating scale questionnaire consisting of 14 items were used in collection of data. Data collected were analyzed using mean (X) and Standard deviation (Std.) The findings of the study revealed that the physical learning environment in primary schools is not sufficiently provided which may affect the quality of teaching and learning in primary school education. It’s also indicated a disagreement in the opinions of teachers and head teachers in GLEA in providing quality aesthetic learning environment at primary school. The Study among others, recommended that The LGEA should be supported and fully involved in decision making and funding of primary education through collaborative effort among all education stakeholders in providing quality attractive learning environment for children not just a supervisory role.